2019
DOI: 10.3920/bm2018.0170
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bifidobacterium breve A1 on the cognitive function of older adults with memory complaints: a randomised, double-blind, placebo-controlled trial

Abstract: In our previous study, we reported the therapeutic potential of Bifidobacterium breve A1 in preventing cognitive impairment in a mouse model of Alzheimer’s disease and participants with mild cognitive impairment; we suggested that probiotic supplementation is an effective therapeutic strategy for managing cognitive function. Accordingly, we conducted a randomised, double-blind, placebo-controlled trial to assess whether 12-week B. breve A1 supplementation could affect the cognitive function of elderly subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(113 citation statements)
references
References 18 publications
2
97
0
Order By: Relevance
“…Conversely, other studies suggested that microbiota depletion may negatively affect cognitive function and microglia and synaptic function in mice and contrasting results were also observed in humans (Laake and Oeksengaard, 2002;Angelucci et al, 2019). Furthermore, a positive effect of probiotics on cognitive function was observed in animal models and AD patients or adults with mild cognitive impairment (Davari et al, 2013;Jiang et al, 2017;Kobayashi et al, 2017Kobayashi et al, , 2019aRezaei Asl et al, 2019;Tamtaji et al, 2019), whereas one study reported no to little effect (Kobayashi et al, 2019b). Erny et al (2015) observed defects of microglia in germ-free mice leading to impaired innate immune responses.…”
Section: Role Of the Gut Microbiota In Disease Symptoms And Pathogenesismentioning
confidence: 98%
“…Conversely, other studies suggested that microbiota depletion may negatively affect cognitive function and microglia and synaptic function in mice and contrasting results were also observed in humans (Laake and Oeksengaard, 2002;Angelucci et al, 2019). Furthermore, a positive effect of probiotics on cognitive function was observed in animal models and AD patients or adults with mild cognitive impairment (Davari et al, 2013;Jiang et al, 2017;Kobayashi et al, 2017Kobayashi et al, , 2019aRezaei Asl et al, 2019;Tamtaji et al, 2019), whereas one study reported no to little effect (Kobayashi et al, 2019b). Erny et al (2015) observed defects of microglia in germ-free mice leading to impaired innate immune responses.…”
Section: Role Of the Gut Microbiota In Disease Symptoms And Pathogenesismentioning
confidence: 98%
“…Probiotics plus selenium intake resulted in significant reduction in high sensitivity CRP, insulin, serum triglycerides, HOMA-IR, VLDL, and LDL levels and significant increase in total antioxidant capacity compared with only selenium and placebo [ 172 ]. In a randomized, double-blind, placebo-controlled study, 12 weeks of B. breve A1 supplementation improved cognitive function in elderly subjects with memory complaints [ 173 ]. In an open-label single-arm study, intake of the same strain B. breve A1 was significantly improved hospital anxiety and depression scale (HADS) score and Positive and Negative Syndrome Scale (PANSS) at four weeks [ 174 ].…”
Section: Interaction Of Gut and Nervous System: Gut–brain Axismentioning
confidence: 99%
“…All studies were randomized, double-blind and controlled trials. Among which, three studies [27][28][29] recruited subjects diagnosed with AD and another two [30,31] included MCI adults. Most studies included a higher ratio of women except for two studies (one [30] had a balanced proportion and the other [28] did not report the sex ratio of the recruited subjects).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The intervention duration of the involved studies was all 12 weeks. Two studies [30,31] used a sole strain of probiotics, while the other three studies applied multiple strains. The study from Azadeh Agahi et al [29] had two active probiotics groups which were regarded as one group for the present analysis.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation